A ação consorciada para elaboração dos planos de gestão municipal integrada e o respectivo sistema de manejo de resíduos sólidos domiciliares nos municípios da região centro sul do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This dissertation deals with an important component of the environmental issue: solid waste. Over the last few centuries waste was correlated with impresatability, not deserving greater attention in relation to it’s management and planning. With the emergence of new technologies, mainly motivated by the process triggered by the Industrial Revolution, new forms of compounds began to be synthesized, which altered the composition of the residues generated in the various human activities. The sum of the production of new technologies, the intensification of the industrialization process and the population density, would lead to the generation of several environmental accidents, especially after the beginning of the 20th century, which were the great motivators for the environmental issue to be discussed at the international level. Since then, several international treaties and agreements have been produced, assimilated in the national legal order. Among these commitments, in 2010, Brazil would issue a National Solid Waste Policy, establishing commitments for all federal entities to prepare their respective waste plans in two years and to implement the environmentally adequate destination in four years. Faced with the legal obligation, focused mainly on the elimination of "landfills", municipalities began to strengthen their inter-municipal bonds, starting to act as consortia, either for the purpose of final disposal of waste or even to elaborate their integrated management plans . The consortium action, promoted by the municipalities of Fernandes Pinheiro, Guamiranga, Inácio Martins, Rebouças, Rio Azul and Teixeira Soares, between 2015 and 2016, in order to carry out their basic sanitation and integrated solid waste management plans is the subject of this dissertation, in the form of case study, through the accomplishment of documentary, bibliographical and field research, this one is directed to the data collection in the municipalities receiving residues, adopting the method of qualitative analysis. The main purpose of this dissertation is to show how management and planning are carried out within small municipalities, regarding the services of removal, collection, transport and final disposal of solid waste that are produced by the residents in their homes, one of the main findings of private management of public interests in relation to the final destination, which was made in private landfills.
Keywords: Resíduos sólidos domiciliares; Município; Plano de gestão; Questão ambiental; Solid residual domiciliary; County; Management plan; Environmental issues; . Basic sanitation; CNPQ::CIENCIAS SOCIAIS APLICADAS